Epidemiological assessment of the first COVID-19 epidemic wave in Lombardy. A systematic review: First COVID-19 epidemic wave in Lombardy - Signorelli, Carlo; Odone, Anna; Gianfredi, Vincenza; Balzarini, Federica; Bucci, Daria; Croci, Roberto; Gaetti, Giovanni; Stirparo, Giuseppe; Guerra, Ranieri (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: After the first cases of COVID-19 detected in Wuhan (China), the virus rapidly spread in the world, so much so that on February 20 the first autochthonous case was officially identified in Italy. However, this person had no apparent history of travel abroad or contact with people tested positive for the virus. For this reason, the aim of this literature review was to reconstruct the epidemiological dynamics of the first wave of SARS-CoV-2 infection in the Lombardy Region.Methods: To this end, a systematic review was carried out on PubMed/MEDLINE and EMBASE, and on grey literature. All article assessing incidence, mortality and hospitalizations by Lombardy province and municipality, and the impact of the main containment and organizational measures were considered eligible. In addition, data on general mortality and mortality due to COVID-19, hospital admission, and serological and environmental were also retrieved.Results: From the included studies, it emerged that Lombardy was the first European region in which the virus began to circulate as early as January 2020 (and probably even earlier). Despite the high number of cases and deaths recorded, the reproduction number observed in Lombardy Region was, at the beginning of March 2020, the same (or lower) than in other regions.Conclusions: In conclusion, data of the first epidemic wave in Lombardy, compared to other Italian and foreign regions, highlight the extreme criticality of having had the first autochthonous case (and the first substantial outbreaks) when knowledge was still scarce and individual prevention measures were not widespread.